AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN HIDROLISAT HASIL HIDROLISIS PROTEIN SUSU KAMBING DENGAN EKSTRAK KASAR BROMELIN - Eni Kusumaningtyas; Raphaella Widiastuti; Harsi Dewantari Kusumaningrum; Maggy Thenawidjaja Suhartono (Jurnal Teknologi dan Industri Pangan, 2015)
Goat milk is highly nutritious foodstuffs that beneficial for improving health. The milk contains bioactive peptides which produced by hydrolysis process. The aim of this study was to evaluate antibacterial and antioxidant activities of hydrolisate produced from hydrolysis of goat milk protein by crude bromelain extract. Hydrolysis of goat milk protein was conducted using crude bromelain (0.1 U/mL) at pH 6, 50°C for 60 min. Hydrolysate was fractionated by using membrane molecular weight cut off 10 kDa. hydrolysate before and after fractionation were assayed for antibacterial and antioxidant activities. Toxicity of the Hydrolysate was determined by hemolysis assay. The result showed that the hydrolysate before and after fractionation inhibited growth of E. coli, S. Typhimurium and L. monocytogenes. Hydrolysate after fractionation has higher antibacterial activity indicated that fractionation was able to improve antibacterial activities of the hydrolysate fraction. The hydrolysate showed scavenging activity to ABTS and DPPH radicals. Fraction <10 kDa has the highest antioxidant activity against both ABTS and DPPH radicals. Hemolysis assay showed that hydrolysate before and after fractionation did not cause lysis of red blood cells, indicating safe for application. Both fraction <10 kDa and >10 kDa not only showed absence of hemolysis but also they were able to reduce autolysis of red blood cells. The result showed that hydrolysate from goat milk hydrolyzed by bromelain were able to be antibacterial and antioxidant.